Discrete mathematical structures with applications to computer science - Tremblay, J. P (Tata McGraw-Hill, 2001)
Discrete mathematical structures with applications to computer science / Tremblay, J. P. -- New Delhi: Tata McGraw-Hill, 2001 511.3 T791 No. of Copies : 1